The rate of electron-transfer reactions in the diffusive limit - Schmickler, W. (Condensed Matter Physics, 2001)
A simple electron-transfer reaction is treated in the diffusive limit, in which the motion of the solvent is governed by the Smoluchowski equation. The electronic transition probability is calculated from the Landau-Zener expression. The rate constant of the reaction is calculated as a function of the strength of the electronic interaction between the reactants. For weak interactions, the rate is the same as that obtained form first-order perturbation theory. For strong interactions, solvent dynamics is rate-determining. The calculations presented here bridge these two limits. Проста реакція електронного переносу розглядається в дифузійній границі, в якій рух розчинника описується рівнянням Смолуховського. Імовірність електронного переходу розраховується з виразу Ландау-Зенера. Константа реакції розрахована як функція сили електронної взаємодії між реактантами. Для слабких взаємодій ступінь реакції співпадає з виразом, отриманим в першому наближенні теорії збурень. Для сильних взаємодій динаміка розчинника визначається ступенем реакції. Представлені розрахунки поєднують обидві границі.